Experiences from the course “Pedagogical Intervention in Preschool Education”: the vision from the faculty trainers, preschool teachers and students - Chaves Álvarez, Ana Lucía (2010)
As part of the educational formation of students from II level of the Associate dregree, from the Pedagogy major with an emphasis on preschool teaching from Universidad Nacional. There is a course named “Pedagogical Intervention in Early Childhood Education” which carries out the process of the intensive practicum. In this article you will find a review of the program’s objetives, experiences and challenges, taking the experiences from the academic team, who have guided this process over the past two years, and the point of views from students and preschool teachers.